Merry Christmas, cowboy - Dailey, Janet (Kensington Books, 2013)
Hoping to give back to the community, Denver police officer Paula Lewis volunteers at the Christmas House to help local children, where she is drawn to local rancher Zach Bennett, as they work together to help a young boy.